REFLECTION OF THE METAPHOR ‘ROAD’ IN CEMIL KAVUKCU’S GAMBA AND THE BEAT’S WRITER JACK KEROUAC’S ON THE ROAD - Memet Metin BARLIK (Fırat University, 2019)
Metaphor that defines perception of a subject with another point of view or associability between the informations in mind has a common usage in literature. However it has seen that numerous authors from ancient time to modern time have handled many different terms which is associated the term of metaphor and have focused on these terms in their own works. The usage of metaphor that nourishes lots of branches such philosophy, sociology, psychology lets author compose different meanings with the words chosen. In this sense the term of ‘road’ which situated in Jack Kerouac’s (1922-1969) On The Road in modern American literature and Cemil Kavulçu’s (1951- ) Gamba in modern Turkish literature have been handled associating with metaphor. In this study it is tried to identify that ‘road’ as ametaphorhow is revealed with which meaning relationship; the way of use in view of philosophic, sociologic, esoteric, mystic and metaphysics. Besides this it is mentioned resemblance and difference in term of road in these novels.